The Advantages and Disadvantages of Breakfast Clubs According to Parents, Children, and School Staff in the North East of England, UK - Graham, Pamela Louise; Russo, Riccardo; Defeyter, Margaret Anne (Frontiers in Public Health, 2015)
The provision of school breakfast has become increasingly popular in the UK in recent years. However, UK-based studies highlighting the views of parents, children, and school staff on school breakfast clubs are lacking. The current study set out to address this dearth in the literature by investigating the views of these key user and stakeholder groups on breakfast clubs within the North East of England. Fourteen parents, 21 children, and 17 school staff were recruited from four primary schools where breakfast clubs were available on site. Parents and school staff took part in semistructured interviews and children participated in focus groups, through which the advantages and disadvantages of breakfast clubs were discussed. Thematic analysis revealed that breakfast clubs provided children with a settled and enjoyable start to the school day. As well as providing children with a healthy and varied breakfast meal and unique opportunities for social interaction, breakfast clubs were recognized as an integral part of the school system that offered support to parents, particularly those who worked and relied on breakfast clubs as a means of affordable and reliable childcare. The few disadvantages identified related to practical issues such as a lack of adherence to school food standards, breakfast club staff missing class preparation time and concerns that some children were being excluded from participating in breakfast clubs particularly due to costs associated with attendance. The findings are discussed in relation to the School Food Plan, and areas for further investigation are proposed.